The Correlation Between Aminotransferase Enzyme Levels, Neutrophil-to-Lymphocyte Ratio, Absolute Lymphocyte Count and the Severity of COVID-19 - Al Sas, Oktafirani; Santosa, Budi; B Suromo, Lisyani; Pranata, Satriya (Scripta Medica, 2023)
Background/Aim: Aspartate aminotransferase (AST), alanine aminotransferase (ALT), neutrophil-to-lymphocyte ratio (NLR) and absolute lymphocyte count (ALC) are indicators that are widely used as a determinant of the prognosis of patients with viral pneumonia. Thus, the study aim was to prove the correlation between AST/ALT, NLR and ALC levels with the severity of COVID-19. Methods: The research method was carried out by collecting medical record data of positive COVID-19 patients who were hospitalised at the Indramayu Hospital in the period September 2020 - January 2021. Results: The results showed normal AST levels in 63 and elevated AST levels in 57 patients. Normal and elevated ALT levels were in 68 and 52 patients, respectively. The normal NLR was in 102 patients and the high NLR was in 18 patients. The low and normal ALC was in 19 and 101 patients, respectively. AST levels correlated with the severity of COVID-19 (p = 0.045). Other parameters were without statistical significance (p > 0.05). Conclusion: AST enzyme levels had a weak positive correlation with the severity of COVID-19. On the other hand, ALT, NLR and ALC had not correlated with the severity of COVID-19.